THE RELATIONSHIP OF SOCIAL MENTALITY AND EDUCATION IN THE PROCESS OF FORMATION OF PERSONAL SOCIAL VIEWS - Associate Professor Talapov Bakhriddin Alijanovich; Otabek Zokirjon Oglu (Scholar Express Journal, 2021)
The article examines the complex elements of social consciousness and examines their structure to form an idea of what laws they apply at the individual and group levels. As in the science of philosophy, it has become customary in political philosophy to distinguish two groups of elements in the analysis of consciousness - the elements related to motivation and cognition.
Keywords: Personality; mentality; social activity; behavior